The primary factor for suture configuration at rotator cuff repair: Width of mattress or distance from tear edge - Onur Hapa; Ahmet Karakaşlı; Onur Başçı; Hakan Cici; Berivan Çeçen; Hasan Havitçioğlu (Acta Orthopaedica et Traumatologica Turcica, 2016)
Objectives: The aims of this study was first to investigate whether the bite size or the bite distance from the tear edge is of primary importance in mattress suture configuration for rotator cuff repair. Secondly, whether the use of a 450 left side bent Arthro-Pierce™ (Smith & Nephew, Andover, USA) during suture passage can be more effective on the strength of the configuration compared to a straight Arthro-Pierce™. Materials and methods: Twenty-eight bovine infraspinatus muscle tendons were randomized into four groups. Group 1; 5 mm wide ‘bite size’ × 15 mm length ‘distance from the tear edge's mattress’; Group 2: 7.5 mm × 10 mm; Group 3: 15 mm × 5 mm ‘using straight Arthro-Pierce™’ and Group 4: 5 mm × 15 mm using left sided 450 bent Arthro-Pierce™. The repair specimens underwent cyclic loading prior to loading the failure testing. Cyclic elongation (mm), peak-to-peak displacement (mm), ultimate load (N), stiffness (N/mm) and failure mode were recorded for each specimen. Results: The mean ultimate load in Group 1 was higher compared to group 3. The peak to peak displacement was higher in Group 4 compared to Group 1 (p < 0.05). The predominant failure mode in Groups 1, 2 and 4 was suture rupture. The Group 3 most specimens failed due to suture cut through the tendon. Conclusion: Bite size from the edge of the tendon seems to be more important than the width of the mattress. The curve of the suture passing device may also have an effect on the strength of the suture tendon interface. Keywords: Rotator cuff tear, Mattress repair